Multidisciplinary care in Stevens-Johnson syndrome - Swapna S. Shanbhag; James Chodosh; Cherie Fathy; Jeremy Goverman; Caroline Mitchell; Hajirah N. Saeed (SAGE Publishing, 2020)
Stevens-Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are potentially fatal mucocutaneous diseases that can involve many organ systems. Manifestations of SJS/TEN outside of the skin, eyes, and oral mucosa are not well defined or well recognized, and, therefore, are often not addressed clinically. As supportive care improves and mortality from SJS/TEN decreases, chronic complications in affected organ systems are becoming more prevalent. Recognition of the manifestations of SJS/TEN in the acute phase is critical to optimal care. In this review, we review the organ systems that may be involved in SJS/TEN, provide an overview of their management, and propose a list of items that should be communicated to the patient and family upon discharge. The organ systems discussed include the pulmonary, gastrointestinal/hepatic, oral, otorhinolaryngologic, gynecologic, genitourinary, and renal systems. In addition, the significant psychosocial, nutritional, and pain consequences and management of SJS/TEN are discussed.